OTONOMI DALAM PELAKSANAAN IBADAH KEAGAMAAN - Muhammad Idrus (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
The aim of this research was to find out (1) the category of worship performing autonomy (2) the difference of worship performing autonomy based on gender and previous school of student; (3) the correlation between age and the degree of worship performing autonomy The data are collected using questionnaire were involved 100 SMA UII student. The mutli stage sampling that is quota stratified proportional random sampling was used as the sampling technique. Desciptif statistic, T test, product moment correlation from Pearson and Two ways theanalaysis of variance are used as the data analysis technique through SPSS for windows program The result of the several analysis towards the data yields several conclusions (1) most of the SMA UII student were in businessman category of worship performing; (2) there is no difference autonomy of worship performing student based on gender and previous school of SMA UII student; (3) there is no correlation of worship performing between ages and the degreeof worship performing category